In situ formation of amorphous Fe-based bimetallic hydroxides from metal-organic frameworks as efficient oxygen evolution catalysts - Xu, You (2022)
Available online 5 April 2021Oxygen evolution from water driven by electrocatalysis or photocatalysis poses a significant challenge as it requires the use of efficient electro-/photo-catalysts to drive the four-electron oxygen evolution reaction (OER). Herein, we report the development of an effective strategy for the in situ chemical transformation of Fe-based bimetallic MIL-88 metal-organic frameworks (MOFs) into corresponding bimetallic hydroxides, which are composed of amorphous ultrasmall nanoparticles and afford an abundance of catalytically active sites. Optimized MOF-derived NiFe-OH-0.75 catalyst coated on glassy carbon electrodes achieved a current density of 10 mA cm−2 in the electrocatalytic OER with a small overpotential of 270 mV, which could be decreased to 235 mV when loading the catalysts on a nickel foam substrate. Moreover, these MOF-derived Fe-based bimetallic hydroxides can be used as efficient cocatalysts when combined with suitable photosensitizers for photocatalytic water oxidation.